Relative yield-per-recruit and management strategies for Cynoscion acoupa (Perciformes: Sciaenidae) in Lake Maracaibo, Venezuela - Ferrer Montaño, Orlando José (2013)
Acoupa weakfish, Cynoscion acoupa, in Lake Maracaibo is subject to intense commercial fishing by an artisanal fleet, and a recent decrease in fish size observed from landings is of concern. This fishery has not yet been modeled, and its assessment and the establishment of management practices to overcome the current overfished condition are urgently needed. To address this, we used recent and past empirical growth estimates to model relative yield-per-recruit under different lengths at first capture. Our results from relative yield-perrecruit analysis showed evidence that growth and recruitment overfishing occur under current fishing practices in Lake Maracaibo. Particular attention was given to fishing practices in El Tablazo Bay where young, small fish predominate in the commercial catches (mean total length=33.7cm), well below the length at first sexual maturity (~40cm TL) for both sexes. As management strategies, we propose to set a mesh size limit at or above 8.89cm (3.5in), which will reduce fishing mortality of immature fish, increase yield-per-recruit, and will result in an increase of Acoupa weakfish recruitment for the long term in Lake Maracaibo.